Endoscopic Endonasal Transclival Approach to the Ventral Brainstem: Anatomic Study of the Safe Entry Zones Combining Fiber Dissection Technique with 7 Tesla Magnetic Resonance Guided Neuronavigation. Issue 2 (10th May 2018) - Weiss, Alessandro; Perrini, Paolo; De Notaris, Matteo; Soria, Guadalupe; Carlos, Alarcon; Castagna, Maura; Lutzemberger, Lodovico; Santonocito, Orazio Santo; Catapano, Giuseppe; Kassam, Amin; Prats-Galino, Alberto
Abstract: BACKGROUND: Treatment of intrinsic lesions of the ventral brainstem is a surgical challenge that requires complex skull base antero- and posterolateral approaches. More recently, endoscopic endonasal transclival approach (EETA) has been reported in the treatment of selected ventral brainstem lesions. OBJECTIVE: In this study we explored the endoscopic ventral brainstem anatomy with the aim to describe the degree of exposure of the ventral safe entry zones. In addition, we used a newly developed method combining traditional white matter dissection with high-resolution 7T magnetic resonance imaging (MRI) of the same specimen coregistered using a neuronavigation system. METHODS: Eight fresh-frozen latex-injected cadaver heads underwent EETA. Additional 8 formalin-fixed brainstems were dissected using Klingler technique guided by ultra-high resolution MRI. RESULTS: The EETA allows a wide exposure of different safe entry zones located on the ventral brainstem: the exposure of perioculomotor zone requires pituitary transposition and can be hindered by superior cerebellar artery. The peritrigeminal zone was barely visible and its exposure required an extradural anterior petrosectomy. The anterolateral sulcus of the medulla was visible in most of specimens, although its close relationship with the corticospinal tract makes it suboptimal as an entry point for intrinsic lesions. In all cases, the use of 7T-MRI allowed the identification of tiny fiber bundles, improving the quality of the dissection. CONCLUSION: Exposure of the ventral brainstem with EETA requires mastering surgical maneuvers, including pituitary transposition and extradural petrosectomy. The correlation of fiber dissection with 7T-MRI neuronavigation significantly improves the understanding of the brainstem anatomy.